Oncologic pathology at an internal medicine service. - de Miranda, M I; da Luz, R; Gonçalves, F M; Monteiro, J S; da Costa, J N (Acta Médica Portuguesa, 1990)
A retrospective survey of the patients with oncological disease admitted to our Department of Internal Medicine in 1987 was conducted to determine its prevalence and to draw a descriptive profile of these patients' admissions. The results show that oncological diseases were the second cause of hospital admissions that year (12%) only exceeded by cardiovascular diseases. About 60% of the patients had neoplasms already diagnosed elsewhere and were admitted for complications or with therapeutic purposes; in 40% of cases the disease was diagnosed in our Department. A wide variety of hematological and non-hematological tumors was found. There were some difficulties in interdisciplinary coordination in the diagnostic and therapeutic approach. More than 50% of the patients had advanced disease, limiting medical intervention to supportive measures. In about 60% of them were oriented to primary care physicians after physicians after discharged from Hospital. These results suggest the dispersion of the available resources for the diagnosis, treatment and follow-up of oncological diseases in our population. A better cancer patients' assistance in Portugal will depend on the promotion of national cancer registers as well as the improvement of cancer prevention and early detection programs, according to the directives of EEC and WHO. We also emphasize the need of investment on undergraduate and postgraduate education programs, specially for primary care physicians.